Prevalence and sociodemographic covariates of infertility in Allahabad district - Kazmi, Samreen; Prakash, Shiv; Parveen, Khurshid; Shaikh, Shama; Prakash, Gyan (International Journal Of Community Medicine And Public Health, 2018)
Background: Childbearing is an extremely important event in every human’s life and is strongly associated with the ultimate goals of completeness, happiness and family integration. Infertility also has important demographic and health implications. TheWorld Health Organization (WHO), using a two year reference period, defines primary infertility as the lack of conception despite cohabitation and exposure to pregnancy and secondary infertility is defined as the failure to conceive following a previous pregnancy despite cohabitation and exposure to pregnancy (in the absence of contraception, breastfeeding or postpartum amenorrhea) for a period of two years. Methods: The study was conducted for a period of one year in randomly selected rural and urban areas of Allahabad district of Uttar Pradesh. Multistage random sampling was done and sample size was calculated out to be 844. Data was collected on a predesigned and pretested questionnaire. Various socio-demographic covariates of infertility were also found. Results: Prevalence of infertility in Allahabad was 8.53%, 11.85% in urban area and 5.21% in rural area. Overall prevalence of primary infertility was 4.98% and secondary infertility was 3.55%. Age of female at the time of marriage, educational and working status of female and socioeconomic status of the couple was found to be significantly associated with infertility. Conclusions: Prevalence of infertility was higher in urban area and overall prevalence of primary infertility was higher as compared to secondary infertility.